2014
DOI: 10.1055/s-0034-1390349
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis in Infants with Ductal-Dependent Congenital Heart Disease

Abstract: Objective Infants with congenital heart disease (CHD) receiving prostaglandins (PGE) may be at increased risk for necrotizing enterocolitis (NEC). Enteral feeding may further increase risk of NEC in these patients. We evaluated the incidence of NEC and its association with enteral feeding in infants with ductal-dependent CHD. Study Design We examined a cohort of infants with CHD receiving PGE in neonatal intensive care units managed by the Pediatrix Medical Group between 1997 and 2010. We used logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 28 publications
1
64
0
2
Order By: Relevance
“… 14 This risk of NEC is higher among single ventricle physiology patients. 15 17 On the contrary, other studies have shown preoperative enteral feeding can be associated with decreased risk of prolonged feeding difficulties postoperatively in some populations and 18 delaying enteral feeding may contribute to increased gut abnormalities and even delayed postnatal intestinal development, maturation, and motility problems. 19 These data suggest the importance of enterally feeding hemodynamically stable patients preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“… 14 This risk of NEC is higher among single ventricle physiology patients. 15 17 On the contrary, other studies have shown preoperative enteral feeding can be associated with decreased risk of prolonged feeding difficulties postoperatively in some populations and 18 delaying enteral feeding may contribute to increased gut abnormalities and even delayed postnatal intestinal development, maturation, and motility problems. 19 These data suggest the importance of enterally feeding hemodynamically stable patients preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important features of this network is its Neonatal Data Warehouse, which includes deidentified data from the neonatal intensive care units in which its doctors practice and the data are derived directly from the electronic medical record of the neonates in each unit on a real-time basis. This data set has been used by the National Institutes of Health, 25,26 the Food and Drug Administration, 27 the Eunice Kennedy Shriver National Institutes of Child Health and Human Development Pediatric Trials Network, 28,29 and others to define and evaluate national trends in neonatal intensive care unit diagnoses and therapies. Ten hospitals were included in this study, including only those which had both Obstetrix MFM practices and Pediatrix neonatology practices.…”
Section: Methodsmentioning
confidence: 99%
“…Многочисленные исследования показали увеличение частоты развития некротизирующего энтероколита у пациентов с врожденными пороками сердца [11][12][13][14][15][16][17]. Частота некротизирующего энтероколита у детей раннего возраста с врожденными пороками сердца колеблется, по разным данным, от 3,3 до 6,8 %, что намного превышает риск развития этого заболевания у новорожденных с неизмененным анатомическим строением сердца [14].…”
unclassified
“…Becker и соавт. [11] показано, что энтеральное кормление не ассоциируется со статистически значимым увеличением частоты развития некротизирующего энтероколита.…”
unclassified